Scaling up agricultural innovations to address hunger and malnutrition - Bouis, Howarth E. (2018)
Howarth Bouis IFPRI-FAO conference, "Accelerating the End of Hunger and Malnutrition" November 28–30, 2018 Bangkok, Thailand